Correlation between metabolite ratios and ADC values of prostate in men with increased PSA level - Kumar, Virendra; Jagannathan, Naranamangalam R.; Kumar, Rajeev; Das, Sharat C.; Jindal, Lokesh; Thulkar, Sanjay; Gupta, Siddhartha D.; Dwivedi, Sadanand N.; Roell, Stefan; Hemal, Ashok K.; Gupta, Narmada P. (Magnetic resonance imaging, 2006)
Proton magnetic resonance spectroscopic imaging (MRSI) and diffusion-weighted imaging (DWI) were carried out in men with increased prostate-specific antigen (PSA) level. Forty subjects [controls (Group I) and patients (Groups II and III with PSA >20 and 4–20 ng/ml, respectively)] were investigated using endorectal coil at 1.5 T prior to transrectal ultrasound (TRUS)-guided biopsy. Metabolite ratio [citrate/(choline+creatine)] and apparent diffusion coefficient (ADC) were calculated for identical voxels. In patients, voxels that showed lower metabolite ratio showed reduced ADC in the peripheral zone (PZ) of the prostate, and voxels with increased metabolite ratio showed higher ADC. Metabolite ratios were used to predict areas of malignancy if the ratio was <1.4 and if ADC value was <1.17×10 −3 mm 2/s. Patients in Group II had lower metabolite ratio and ADC in the PZ compared to controls and Group III. All 13 were positive for malignancy in MR, while 12 of 13 were positive on TRUS-guided sextant biopsy. In Group III, certain voxels of PZ that showed reduced metabolite ratio also showed lower ADC. A positive correlation was observed between metabolite ratio and ADC. MR predicted areas of malignancy in PZ in 15 of 20 patients; however, only six were positive on TRUS-guided biopsy perhaps due to high false-negative rate of TRUS-guided biopsy. Results show positive correlation between MRSI and DWI and their potential in detection of malignancy, thereby improving the diagnosis especially in patients with PSA level of 4–20 ng/ml.